Congenital cytomegalovirus (CMV) for the pediatric otolaryngologist. (September 2021) - Prosser, J. Drew; Holmes, Thomas W.; Seyyedi, Mohammad; Choo, Daniel I.
Abstract: Cytomegalovirus (CMV) is a double-stranded DNA virus and a member of the herpesvirus family. It is the most common congenital viral infection. For symptomatic infections, symptoms can vary widely but tends to have a predilection for the central nervous system and for the reticuloendothelial system. Sensorineural hearing loss (SNHL) is by far the most common sequelae of congenital CMV infection. For this reason, it is imperative to understand the screening, diagnosis, and possible treatment options for congenital CMV induced SNHL. This literature review explores the association of CMV with hearing loss, screening for congenital CMV infections, possible treatments options, and the development of a possible vaccine.